ANALISIS PENGAKUAN PENDAPATAN DAN BEBAN PADA PT. BANK PEREKONOMIAN RAKYAT SEJAHTERA BATAM - Mariansah, Darman; Prima, Argo Putra (LPPM Universitas Putera Batam, 2025)
Rural Banks (Bank Perekonomian Rakyat) are a type of financial institution that operates within Indonesia’s banking sector. This study was conducted to analyze the income statement of PT Bank Perekonomian Rakyat Sejahtera Batam over the past five years, as well as to examine the process of revenue and expense recognition. The research employs a descriptive qualitative approach. The objective is to identify and understand revenue and expense recognition in the bank’s operational activities and to explore various challenges associated with this recognition process. The findings of this study may influence corporate decision-making and are expected to provide valuable insights for readers.